The Successive Metamorphoses of the Protagonist as a Literary Theme in The Story of Joseph from de Hebrew Bible and the Neo-Egyptian Tale of The Two Brothers - Salvador, Adriana Noemí (2023)
Once the comparative study between the story of the New Kingdom of The Two Brothers and The Story of Joseph in the Hebrew Bible has been established, the last theme of the transformations that the protagonist will undergo is analyzed from intertextuality. It considers the historical-geographical context, the intentionality, and the characteristics present during creation of the writing in which the story came to us, the Biblical Hebrew that has its origin in the Proto-Sinaitic. The latter, created in the Sinai Peninsula during the Middle Kingdom; the tradition of the narrative that we study, in the Jewish colony of Elephantine around the Axial period, circa the 6th century B.C. Thanks to lexical morphosemantics, the materiality of the text, which we propose as a “bridge text” in the Torah, is connected with the embodied cognition of the contemporary reader who remains inserted in the plot and we believe can participate in it as a “rite of passage”.